2011
DOI: 10.3892/mmr.2011.425
|View full text |Cite
|
Sign up to set email alerts
|

Unbalanced MMP/TIMP-1 expression during the development of experimental pulmonary fibrosis with acute paraquat poisoning

Abstract: Abstract. Paraquat (PQ)-induced pulmonary toxicity is known to result in pulmonary edema, infiltration of inflammatory cells and damage to the alveolar epithelium, which may progress to severe fibrosis. Matrix metalloproteinases (MMPs) and their physiological inhibitors, tissue inhibitors of matrix metalloproteinases (TIMPs), which degrade and remodel the excess extracellular matrix, are believed to play an important role in the development of fibrotic tissue. In this study, we examined the sequential expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 21 publications
1
14
0
Order By: Relevance
“…(data not shown) In addition to these data, we investigated the presence of fibrosis in lungs after CBDL using Masson trichrome staining, since we assumed that our model had the possibility of causing pulmonary fibrosis due to the high level of MMP expression. [20][22] However, the results showed that our model did not induce the development of pulmonary fibrosis at either 2 or 3 weeks after CBDL compared with sham operated mice (data not shown).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…(data not shown) In addition to these data, we investigated the presence of fibrosis in lungs after CBDL using Masson trichrome staining, since we assumed that our model had the possibility of causing pulmonary fibrosis due to the high level of MMP expression. [20][22] However, the results showed that our model did not induce the development of pulmonary fibrosis at either 2 or 3 weeks after CBDL compared with sham operated mice (data not shown).…”
Section: Resultsmentioning
confidence: 73%
“…In our model, the reason that lung fibrosis, which was assessed with Masson trichrome staining, was not strongly induced might be explained as follows; firstly, MMP-9, which is secreted from increased neutrophils during inflammation plays a role in suppression of fibrosis in the tissue [20]. Secondly, unbalanced MMP and TIMP expression during the time course we used was reported to contribute to development of experimental pulmonary fibrosis: lung MMP-2 and MMP-9 m-RNA levels have peak levels and less pulmonary fibrosis is present 1 week after induction, while MMPs inhibitors, such as TIMPs, have a different peak and are present at higher levels 3 weeks after pulmonary fibrosis induction [21], [22] Lastly, the mice strain used, which was Balb/c, might have affected the development or severity of pulmonary fibrosis, as Walkin et al described that this strain is resistant to pulmonary fibrosis, but susceptible to hepatic fibrosis. [41] …”
Section: Discussionmentioning
confidence: 99%
“…In our study, MMP‐1, MMP‐9 and TIMP‐1 mRNA were significantly elevated in the lung after bleomycin‐induced injury and development of fibrosis. However, in the late phase of disease, production of MMP‐9 was gradually decreased, but the expression of TIMP‐1 continued to rise, which may lead to a MMP‐9/TIMP‐1 imbalance, resulting in ECM accumulation and remodelling [26,35,36] . Coadministration of DBTG with bleomycin reduced the bleomycin‐induced elevation in lung MMP‐9 mRNA levels, and particularly decreased TIMP‐1 expression, which determined the nature of the remodelling process.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the destruction of the basement membrane, which regulates lung epithelial permeability, may promote migration of fibroblasts, as well as deposition of the alveolar cavity collagen fiber, and cause pulmonary fibrosis. TIMPs are endogenous inhibitors of MMPs, and it has been demonstrated that the MMP/TIMP and ECM metabolic imbalance is involved in the development and progression of pulmonary fibrosis (32). Selman et al (33) showed that in patients with IPF, dominant active TIMP expression resulted in filamentous collagen degradation, which caused the occurrence of pulmonary fibrosis.…”
Section: Discussionmentioning
confidence: 99%